Application of light-emitting diodes (LEDs) fishing lights to improve catch rates of small-scale trammel net fishery in the Yellow Sea, China - Yu, Mengjie; Liu, Changdong; Zhang, Liyou; Tang, Yanli (Frontiers in Marine Science, 2022)
The small-scale trammel net fisheries are essential to the economy and well-being of coastal communities in the Yellow Sea, China. However, these fisheries are low efficient and urgently demand technical innovations to improve catch rates. In this study, we conducted field experiments in three traditional fishing grounds (Rizhao, Yantai, and Weihai) to test whether the addition of different colored light-emitting diodes (LEDs) fishing lights in the trammel nets could improve the catch rates of seven commercial species. Results showed that the effects of LEDs on catch rates were species-specific. Green LEDs could significantly increase the catch per unit effort (CPUE) of black rockfish (Sebastes schlegelii), fat greenling (Hexagrammos otakii), marbled flounder (Pseudopleuronectes yokohamae), stone flounder (Platichthys bicoloratus), Asian paddle crab (Charybdis japonica), and mantis shrimp (Oratosquilla oratoria) by 40%-72% compared with unilluminated nets, while had no significant effect on the catch rates of swimming crab (Portunus trituberculatus). Red LEDs harvested 58%-86% higher CPUE of fat greenling, marbled flounder, stone flounder, mantis shrimp, and swimming crab while catching fewer black rockfish and Asian paddle crab. Blue and white LEDs exhibited similar performance, which could significantly capture more black rockfish, fat greenling, and mantis shrimp and did not affect the catch rates of other species. The effects of LEDs were also size-dependent for certain species, and the catch rates generally increased with the length classes. Taking economic benefits into consideration, the green and red LEDs provided the highest profitability for Rizhao, while green LEDs performed best in Weihai and Yantai. This study is the first investigation on how artificial lights affected the catch rates of trammel nets. The findings of our study illustrated that trammel nets equipped with LEDs could serve as a viable fishing strategy in small-scale trammel net fisheries.